Adult Attachment Representations and Body Image - Bonev, Nikolay; Matanova, Vanya (Frontiers in Psychology, 2021)
In modern literature, the body image is interpreted as a multidimensional construct, which is considered important for both individual development and quality of life. The body image is central to the self-concept and has important consequences for mental functioning. A negative body image can result in adverse psychosocial consequences for both sexes. For a long time in the professional literature the study of socio-cultural factors on the development of the body image has prevailed. This line of research creates social constructivism, in which the earliest attachment relations are eliminated, and instead the idea is suggested that external sources have a direct influence. The present text proposes an approach to the body image as a development construct, arising and developing in the attachment relations, related to the provision of security and protection. Attachment disturbances, as well as attachment disorganization, are defined as the inability to provide security and protection. Attachment relationships in connection with the development of body image develop through the mechanisms of reflection, sensitive responses to the child's signals and synchronous relationships. In the first months of human life, the attachment needs are first and foremost the needs of the body, which are satisfied by the responses of the primary caregiver. The topic of body image discusses attachment disorganization, the understanding of attachment trauma, and the "enactment" of the loss on the body`s territory. Trauma always involves loss. Griefs that cannot be mourned and injuries that cannot be represented seem to be central to understanding the body's problematization.